2013
DOI: 10.1016/j.cbpa.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of [U-2H7]glucose into hepatic glycogen in rat and in seabass

Abstract: The stimulation of hepatic glycogenesis is a ubiquitous response to a glucose challenge and quantifying its contribution to glucose uptake informs its role in restoring euglycemia. Glycogenesis can be quantified with labeled water provided that exchange of glucose-6-phosphate hydrogen 2 (G6P-H2) and body water via glucose-6-phosphate isomerase, and exchange of positions 4, 5 and 6 hydrogens (G6P-H456) via transaldolase, are known. These exchanges were quantified in 24-h fasted rats (Rattus norvegicus; n=6) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…It also explains the high rates of futile glucose–G6P cycling observed under feeding conditions since both GK and G6Pase are active at the same time ( 13 , 32 , 45 ) . Metabolic fluxes obtained from 2 H NMR in the present study and other studies ( 46 ) associated with the lack of response observed in pyruvate kinase (present study), and PFK-1 ( 45 , 47 ) , located downstream of G6P in the glycolytic pathway, seem to support this assumption. Along with this futile cycling of glucose, the contribution of glycogen conversion to glucose via glycosidases ( EC 3.2.1, includes glucosidases, amylases and glycogen-debranching enzymes) is yet to be evaluated.…”
Section: Discussionsupporting
confidence: 88%
“…It also explains the high rates of futile glucose–G6P cycling observed under feeding conditions since both GK and G6Pase are active at the same time ( 13 , 32 , 45 ) . Metabolic fluxes obtained from 2 H NMR in the present study and other studies ( 46 ) associated with the lack of response observed in pyruvate kinase (present study), and PFK-1 ( 45 , 47 ) , located downstream of G6P in the glycolytic pathway, seem to support this assumption. Along with this futile cycling of glucose, the contribution of glycogen conversion to glucose via glycosidases ( EC 3.2.1, includes glucosidases, amylases and glycogen-debranching enzymes) is yet to be evaluated.…”
Section: Discussionsupporting
confidence: 88%
“…Hepatic glycogen levels were also significantly different between fasted seabream and fasted seabass ( P < 0.0005, respectively). Compared to our previous study with 90 g fasted seabass 9 , liver glycogen levels were somewhat higher: 8.4 ± 0.5 g.100 g −1 liver in this study versus 6.6 ± 0.6 g.100 g −1 liver previously. From a comparison of hepatic glycogen levels in saline-injected versus glucose-injected seabass, the glucose load resulted in a significant increase in hepatic glycogen levels of fasted fish while it had no significant effects on glycogen levels of fed fish (Table 1 ).…”
Section: Resultscontrasting
confidence: 96%
“…In the 2 H NMR spectrum, the position 2 intensity appears to be less than that of position 5 - consistent with a previous seabass study of glycogen enrichment from 2 H 2 O 13 . This is due to a significant kinetic isotope effect that limits the exchange between the hydrogen 2 of G6P and body water 9 thereby decreasing the enrichment of this specific site from 2 H 2 O. The magnitude of this effect can be quantified from the analysis of glycogen 2 H-enrichment from [U- 2 H 7 ]glucose allowing the position 2 enrichment from 2 H 2 O to be corrected for incomplete exchange 9 (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G-6-P, glucose-6-phosphate; Gly-3-P, glyceraldehyde-3-phosphate; DHAP, dihydroxyacetone phosphate; OA, oxaloacetate; PEP, phosphoenolpyruvate; AA, amino acids. stable isotope tracer methodologies, that are highly practical for juvenile fish raised in small recirculating systems in the research setting (Viegas et al, 2012(Viegas et al, , 2015(Viegas et al, , 2016Martins et al, 2013;Rito et al, 2018Rito et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%